Numerical study of the Navier–Stokes-α deconvolution model with pointwise mass conservation. Issue 9 (2nd September 2018) - Breckling, Sean; Neda, Monika
ABSTRACT: This paper presents an efficient, universally stable finite-element scheme for the NS α deconvolution model. Accuracy is enhanced by van Cittert approximate deconvolution, as well as through the choice of pointwise divergence-free discrete spaces. Finite-element analysis is provided, which includes results for stability, well-posedness, and optimal convergence of both velocity and pressure solutions. Finally, several numerical experiments are presented which demonstrate the performance of NS α, as well as illustrate the advantages of pointwise divergence-free finite elements.